2012
DOI: 10.1590/s1516-89132012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Selection of cellulolytic fungi isolated from diverse substrates

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…There have been abundant reports during the last decade about biological fungicides by solid substrates and optimizing production procedures (Pascual et al 1999;Budge and Whipps 2001;Schuster and Schmoll 2010;Damaso et al 2012;Sargin et al 2013). For instance, Pascual et al (1999) showed the solid biological fungicide containing the fungus Epicoccum nigrum on wheat.…”
Section: Introductionmentioning
confidence: 99%
“…There have been abundant reports during the last decade about biological fungicides by solid substrates and optimizing production procedures (Pascual et al 1999;Budge and Whipps 2001;Schuster and Schmoll 2010;Damaso et al 2012;Sargin et al 2013). For instance, Pascual et al (1999) showed the solid biological fungicide containing the fungus Epicoccum nigrum on wheat.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of carboxymethyl functional groups (the degree of substitution: 0.65-0.90) suppresses the exoglucanase (EXG) activity which could The mean values given in columns with different letter index are significantly different (α < 0.05); Group 1 -selected isolates which had the highest RS values while grown under submerged fermentation (SmF) with 1.0% CMC; Group 2 -selected isolates which had the highest EI values while grown on solid state media with CMC; Significant differences were determined separately for group 1 and group 2; X -unidentified fungus affect either the RS amount or the hydrolysis degree (Zhang et al, 2006). For EI determination, Damaso et al (2012) and Goldbeck et al (2012) used celluloses other than CMC, e.g., microcrystalline cellulose: Avicel or Servacel. For cellulase activity determination, at the next selection stages, various cellulose types were applied: Servacel (Goldbeck et al, 2012); Whatman No.…”
Section: Application Of Cmc As a Substratementioning
confidence: 99%
“…For cellulase activity determination, at the next selection stages, various cellulose types were applied: Servacel (Goldbeck et al, 2012); Whatman No. 1 filter paper (Ruegger and Tauk-Tornisielo, 2004;Jahangeer et al, 2005;Florencio et al, 2012); and wheat bran (Ruegger and Tauk-Tornisielo, 2004;Damaso et al, 2012;Florencio et al, 2012). Application of cellulose with different physicochemical properties can affect the activity of cellulases.…”
Section: Application Of Cmc As a Substratementioning
confidence: 99%
See 2 more Smart Citations